Pengembangan Alat Permainan Engklek Untuk Menstimulasi Kemampuan Motorik Kasar Pada Anak Usia Dini Di PAUD Swadaya - Masganti Sitorus; Salsabilah Salsabilah; Septia Putri Anggraini; Syahdia Shinta Simanjuntak; Yola Adela Sindy; Ziha Fida Utami Tanjung (Peneliti.net, 2023)
The aim of the study was to develop a crank game tool that can be used effectively to stimulate gross motor skills in early childhood at Swadaya PAUD. The crank game tool was chosen because this game involves body movements that can stimulate the development of gross motor skills in children. The research method used is the development research method. The stages in this development method include initial design, limited trials, evaluation, and revision of game tools. In the initial design stage, identification of needs and design of the concept of a crank game tool were carried out. Then, prototypes of game tools are made based on this design. After that, a limited trial was carried out involving a group of early childhood children at PAUD Swadaya. This trial aims to test the feasibility and effectiveness of the developed crankshaft game tool. During the trial, observations were made on children's responses and participation in using the crank game. Furthermore, an evaluation was carried out through observation and interviews with teachers and parents of the children involved in the trial. This evaluation aims to obtain input and responses regarding the effectiveness of the crank game in stimulating children's gross motor skills. Based on the results of the evaluation, revisions were made to the crankshaft to improve and refine its design. This revision was carried out taking into account the input and suggestions provided by teachers, parents and children involved in the research. The results showed that the crankshaft game developed in this study was effective in stimulating gross motor skills in early childhood at PAUD Swadaya. Children showed an increase in gross motor skills after using the crank game. This shows that the crank game tool can be an effective tool in developing gross motor skills of early childhood. This research makes an important contribution in the context of PAUD Swadaya, because it presents alternative games that can be used to stimulate children's gross motor development in a fun and interactive way. The hopscotch game tool that was developed can be used as a useful educational strategy in improving gross motor skills of early childhood.